A structural study of Acacia nilotica and Acacia modesta gums - Massey, Shazma; MacNaughtan, William; Williams, Huw E.L.; Wolf, Bettina; Iqbal, Mohammad S. (Elsevier, 2017)
Superficially similar carbohydrate polymers from similar sources can have dramatically different characteristics. This work seeks to examine the molecular properties responsible for these differences. Protons responsible for cross-polarization in the anomeric region of Acacia nilotica (AN) were replaced easily by deuterium, but not for Acacia modesta (AM). Time constants describing the mobility and cross-polarization transfer were both found to be lower for AM. Variable contact time experiments showed poorer fits and more heterogeneity for AN. Solution state HSQC experiments showed a lower number of environments in the anomeric region for AM. The relaxation time T2 of AM solutions had a lower value consistent with a higher viscosity. The Tg′ of solutions were −14.5 °C AN and −18.5 °C AM. These results form a largely self-consistent picture of molecular differences between AN and AM, suggesting a more compact but heterogeneous structure for AN and more branching in the case of AM.